Characteristics of Addition of Activated Carbon and Bentonite Clay Catalysts in the Pyrolysis of Polyethylene Terephthalate Plastic Waste - Dianta Mustofa Kamal (Polinema Press, Politeknik Negeri Malang, 2022)
The increase in the use of plastic results in an increase and accumulation of the volume of plastic waste which causes environmental problems, because plastic is an inorganic material that is very difficult to decompose in nature. This research was conducted to utilize Polyethylene Terephthalate (PETE) plastic waste into liquid fuel by pyrolysis method using a catalyst in order to increase the yield of liquid products and the quality of the liquid fuel produced. The research method is carried out by making a simple reactor to obtain liquid fuel, after the product is produced, the yield is calculated, and the density, viscosity, and calorific value are tested. The results of this study prove that the use of bentonite clay catalyst produces a higher yield of about 4.1% to 6.7% than the use of activated carbon catalyst with a yield of 21.74% and a heating value ranging from 10572 to 10860 cal/ g. Likewise, the density and viscosity of the product are still classified as meeting the quality standards of commercial fuel oil (BBM).